EFEKTIVITAS MODEL PROBLEM BASED LEARNING BERBANTUAN BUTIK TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA PADA MATERI STATISTIKA DATA TUNGGAL: Array - Sholihat, Rojatun; Amalia, Sofri Rizka (Jurnal Dialektika Program Studi Pendidikan Matematika, 2019)
This research is bades on the low ability of student’s matematical problem solving. The result of midterm examination on the second semester in mathematical subject for eighth grade student in the academic year 2018/2019 showed that the average score of the students was 56,46, and it means that many of the students have not been able to pass the standard KKM of 70. The objective of this study was to find out effectiveness of Problem Based Learning assisted with BUTIK on the ability of solving mathematical problems especially in Single Data statistics subject. The effectiveness seen from the compare of Problem Based Learning assisted by BUTIK with conventional models on achieving minimum completeness criteria (KKM) and the better comparison or not between BUTIK assisted Problem Based Learning with conventional learning models. The researcher used Posttest-Only Control Design in this research. The samples of this study were chosen by the used of Cluster Random Sampling. The data were analyzed by using normality, homogeneity, average, completeness, and comparison. The result of this study showed that Problem Based Learning assisted with BUTIK was effective in mathematical problem solving’s ability of the students.